Chapter Footwear Innovation to Improve the Comfort of Use - Masłowska-Lipowicz, Iwona; Słubik, Anna; Wyrębska, Łucja; Miśkiewicz, Katarzyna; Adamczyk, Magda; Lasoń-Rydel, Magdalena (Wydawnictwo Uniwersytetu Łódzkiego, 2025)
undefined